2004
DOI: 10.1002/pits.20013
|View full text |Cite
|
Sign up to set email alerts
|

Childhood‐onset schizophrenia: An overview

Abstract: Childhood-onset schizophrenia (COS), particularly when diagnosed prior to the age of 13, is considered to be especially rare and severe. This article provides an in-depth look into its symptomatology, general course, long-term functioning, diagnostic criteria, and methods of assessing the disorder. It also includes discussions of the various treatments used with patients having COS, including psychopharmalogical treatments, cognitive therapy, family interventions, educational interventions, and environmental m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…For instance, males show much higher incidence of schizophrenia and developmental disorders (Fombonne, 2005; Gonthier and Lyon, 2004). Females, however, are more susceptible to neurodegenerative disorders and mood disorders (Barnes et al, 2005; Hebert et al, 2013; Piccinelli and Wilkinson, 2000; Zhao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, males show much higher incidence of schizophrenia and developmental disorders (Fombonne, 2005; Gonthier and Lyon, 2004). Females, however, are more susceptible to neurodegenerative disorders and mood disorders (Barnes et al, 2005; Hebert et al, 2013; Piccinelli and Wilkinson, 2000; Zhao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of schizophrenia in children and adolescents is rather low, with estimates of VEOS varying between 1 in 10.000 [21], 1 in 30.000 in children before age 13 [13], and 1.4 in 10.000 before age 15 [26]. Among patients with schizophrenia, a Finnish study found that 4.7% had onset at or before age 18 [27].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on outcome of EOS have been restricted to small samples and/or short follow-up periods. The results are inconclusive across studies with some showing a prognosis resembling that of AOS but most reporting poorer prognosis [21,23,34,38,41]; only a few studies do not concur with this trend [42-44]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence rates for the disorder are low, with estimates at 1 in 10,000 (Dulmus & Smyth, 2000). Although there is currently no evidence-based treatment for COS, treatment strategies for this disorder generally consist of an array of interventions including pharmacological therapy, cognitive restructuring, educational interventions, environmental manipulations, and family therapy (McClellan et al, 2001;Gonthier & Lyon, 2004).…”
mentioning
confidence: 99%